Effects of a psychosocial intervention programme combined with exercise in community‐dwelling older adults with chronic pain: A randomized controlled trial. (21st November 2017) - Hirase, T.; Kataoka, H.; Nakano, J.; Inokuchi, S.; Sakamoto, J.; Okita, M.
Abstract: Background: Although researchers have recommended exercise training and psychosocial intervention to manage chronic pain, an effective intervention for Japanese community‐dwelling older adults with chronic pain has not been established. This randomized controlled trial examined whether exercise training combined with psychosocial intervention more effectively improves pain, psychological status and physical activity than does exercise training alone in this population. Methods: We randomized 128 older adults with chronic pain to either an intervention group ( n = 64) involving exercise training combined with psychosocial intervention, or a control group ( n = 64) involving only exercise training. Exercise training comprised weekly 60‐min sessions for 12 weeks. Psychosocial intervention involved changing participants' focus on pain using self‐management education and cognitive behavioural therapy, and participants recorded their daily pain intensity and step counts. Pain intensity, psychological status and physical activity were assessed before and 12 weeks after the intervention. Results: A time‐by‐group interaction emerged for psychological status ( p = 0.003) and physical activity ( p < 0.001), both favouring the intervention group. The intervention group also showed greater improvement in pain intensity at 12 weeks than did the control group ( p = 0.007). Conclusions: Exercise training combined with psychosocial intervention improves key outcome indicators more effectively than does exercise training alone in older adults with chronic pain. Significance: Although research has shown that combined exercise and psychosocial intervention is optimal for managing chronic pain, our study is the first, to the best of our knowledge, to test a specific intervention of this type in community‐dwelling older adults with chronic pain in Japan.